Remote process control and monitoring by using TCP/IP - Nurul Izyan, Ahmad Tarmizi (2008)
This project presents a practical approach to monitor and control the process in industries by computer using TCP/IP connection. Transmission Control Protocol (TCP) and the Internet Protocol (IP) are the protocols for communication on the Internet where a stream of data that is sent over the Internet is first broken down into packets by the TCP and IP is responsible for sending the packet to its destination along a route. The system contains two main parts that is a local digital controller and graphical user interface (GUI) application. The local digital controller which controls the system is implemented on a PIC18F4620 microcontroller. The graphical user interface (GUI) application by using visual basic makes the users easier to monitor and control the system when uses TCP/IP protocol. The user can monitor and control the process by using computer. Programming software also will be used to program this microcontroller. By using this TCP/IP on this project, a lot of advantages we can get such as the user can be at any place to monitor and control the system as long as they have computer along with the internet connection. It also can maintain the productivity and prevent losses of the product in industries.